Whiteness After 9/11 - Thomas Ross (Washington University Journal of Law & Policy, 2005)
In this Essay, I explore a particular set of ripples outward from 9/11, namely, the effects on the racial identity we call “being White.” I want to show that these contemporary ripples are part of a historical narrative about national identity that runs like a thread through our nation’s history. This narrative about “America” expresses the notion of White supremacy through an amalgam of civic and racial nationalism and thus serves to assuage the racial anxiety of White Americans at a time when that reassurance is perhaps most needed. This will be tricky business. Tracing threads from one historical event to another and then from those events to a cultural conception like “being White” is always a reductive and speculative enterprise. That is, the myriad variables always shroud both the past and the present and make our causal claims suspect. Nonetheless, as we struggle to better understand our contemporary circumstances, what better tools do we possess than to look back as best we can? Looking back at various historical moments, the idea of America as a White, Christian nation with a special destiny has taken center stage. We seem to live today in such a moment. In this Essay, I seek to support that hypothesis and discuss its unsettling implications.
Keywords: Critical race theory; Nationalism; September 11 Terrorist Attacks; 2001